Aplicación de un modelo de mejoramiento a la productividad laboral basado en la metodología DMAIC en una empresa fabricante de alimentos (2021)
The factory dedicated to the food sector, which consists of several plants inside and from which the study of the application of the six sigma’s methodology will be emphasized, is the packaging line for chocolate-based products, for this reason The factory is committed to continuous improvement, in terms of Six Sigma, this is one of the main strategies that several of the world's leading companies have used for more than a decade, and thanks to its successful application they have generated millionaire profits, This degree project addresses one of these practices, with the design of the DMAIC system in the packaging and packaging process, aimed at reducing the cost of labor per cardboard produced, following this methodology an improvement analysis was made to find and eliminate the causes of errors, defects and delays in the processes of the packaging and packaging line, focusing on those aspects that are critical for the organization, d designed and promoted by the senior management of the organization, in which projects are developed in the different areas of the company with the aim of achieving